Development of a Research-Based Learning Model Integrated with Character Education (RBL-ICE) in Basic Science Course - Mutmainah, Mutmainah; Reksamunandar, Rhyan Prayuddy; Mokoginta, Aulia Revalina; Rahman, Fadzilah Abd (Journal of Elementary Educational Research, 2025)
The lack of integration between research-based learning and character education remains a major challenge in Islamic higher education today, where students are required to master 21st-century skills while also developing strong character and academic integrity. This study aims to develop a Research-Based Learning model integrated with Character Education (RBL-ICE) and its associated instructional devices for the Basic Science course. The study employed a Research and Development (R&D) approach with the 4D model (define, design, develop, disseminate). The population comprised all Madrasah Ibtidaiyah (MI) pre-service teachers enrolled in the Basic Science course at IAIN Manado. The sample consisted of 15 students selected through purposive sampling. The measured variables included learning outcomes, learning motivation, and student character. Learning outcomes were obtained through pretest and posttest, learning motivation was measured using a questionnaire based on the ARCS model, and character was assessed using observation sheets. The validity of the model and instructional devices was evaluated by two material experts and two media experts. The material experts rated the research instruments, lesson plans, teaching materials, and student worksheets as very feasible, while the media experts rated the student worksheets and teaching materials as very feasible. Learning outcomes data were analyzed using prerequisite tests (normality) and hypothesis testing with a paired sample t-test, whereas motivation and character were analyzed descriptively. The implementation of the RBL-ICE model improved students’ learning outcomes, with an average pretest score of 66.67 and posttest score of 77.07, and an N-gain of 0.3271 (moderate category), accompanied by increased motivation and character in the positive category. These findings indicate that the RBL-ICE model is effective in enhancing the learning outcomes, motivation, and character of prospective MI teachers in the Basic Science course at IAIN Manado.